2016
DOI: 10.1016/j.matdes.2016.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Elastomer-metal laminate armor

Abstract: • Polymer-aluminum laminates on the strike-face of steel plates enhance ballistic performance.• With judicious selection of substrate and laminate, a broad range of performance and weight combinations can be obtained.• There is both a reduction in magnitude of the substrate deformation and spatial dispersion of the impact.• The main function of the metallic layers is to stiffen the polymer without affecting the latter's viscoelasticity response. A study was carried out of pressure wave transmission and the bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Other studies had found that polymeric coating increases the impact resistance of hard substrates, such as metal or composite structure [6][7][8][9][10][11]. Amini et al [6] investigated the effect of a polyurea layer casted on the back of a plate under dynamic shock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies had found that polymeric coating increases the impact resistance of hard substrates, such as metal or composite structure [6][7][8][9][10][11]. Amini et al [6] investigated the effect of a polyurea layer casted on the back of a plate under dynamic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found that the blast resistance effect of a thicker coating on the back surface was superior than that of a thinner one. Roland et al [8,9] applied elastomeric coatings on the front face to enhance the ballistic resistance of steel armor under impact loading generated by a highspeed projectile. Furthermore, polymer-metal laminates were also used to improve the ballistic performance, and they provided superior ballistic protection than uniform polyurea coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a coating suggested in Anti‐Erosion Structure For Aircrafts for leading edge of aircrafts includes hard thin coatings and superposition of ductile and stiff layers, where ductile layers act as dampers and absorb shocks. For the armor enhancement, especially for “higher severity threats,” multilayered elastomer coatings with alternating soft polymer/stiff metal layers were proposed . The impact protection properties of this multilayer system are sufficiently better than common protection.…”
Section: Discussionmentioning
confidence: 99%
“…For the armor enhancement, especially for "higher severity threats," multilayered elastomer coatings with alternating soft polymer/stiff metal layers were proposed. 23,24 The impact protection properties of this multilayer system are sufficiently better than common protection. Also, Jayachandran et al 25 studied the effect of placement of different material layers in a multilayer coating under indentation on stress state and failure.…”
Section: Multilayers/alternating Layersmentioning
confidence: 94%
“…For the armour enhancement, especially, for “higher severity threats,” multilayered elastomer coatings, with alternating soft polymer/stiff metal layers were proposed . The impact protection properties of this multilayer system are sufficiently better than common protection.…”
Section: Multilayer Coatings and Interfacesmentioning
confidence: 99%